'He needs pulling down a peg or two': Assessing online fan responses to racialized discourse in sports broadcasting. (1st June 2021) - Kilvington, Daniel
Although overt expressions of racism are increasingly rare within the sport media, implicit and conscious/unconscious racial bias, on the other hand, is a common feature within contemporary sports reporting. A comprehensive body of research has illustrated that Black athletes are more likely to be praised for their supposed innate biological superiority while White athletes are more likely to be credited for their work ethic and intelligence. In addition, Black, Asian and minoritized ethnic athletes, such as Lewis Hamilton and Raheem Sterling, have often been criticized for being too 'flashy' by some sections of the UK press, which conjures up images of undeserved riches. These representations are symptomatic of a wider culture in which minoritized communities are 'othered'. This article, then, focuses on one example of racial bias from BBC Radio Derby's Sports Scene podcast from February 2020. Former professional footballer turned pundit, Craig Ramage, suggested that 'all the young Black lads' needed 'pulling down a peg or two' and needed to work harder. This work empirically investigated three online post titles across Facebook, Instagram and a forum to critically examine how contemporary football audiences reacted to such comments. The analysis illustrated that online participants were: (1) divided over whether Ramage's comments were racist or not, (2) unsure of who was to blame, (3) unsure of who the victim was. The article concludes by outlining preventative measures to avoid such reoccurrences and emphasizes the importance of educational training around equality and diversity within the sport media.